2023
DOI: 10.3390/diagnostics13030364
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Exercise and Rehabilitative Implications in the Process of Nerve Repair in Peripheral Neuropathies: A Systematic Review

Abstract: Background: The various mechanisms involved in peripheral nerve regeneration, induced by exercise and electrical nerve stimulation, are still unclear. Objective: The aim of this review was to summarize the influence of physical exercise and/or electrical stimulation on peripheral nerve repair and regeneration and the variatio nerve stimulationn of impact of intervention depending on timing, as well as kind and dosage of the intervention. A literature survey was conducted on PubMed, Scopus, and Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Regeneration is estimated to a rate of nearly about 1 mm/day [ 30 , 32 ] and different nerve conduction studies (NCS) have been used [ 33 , 34 , 35 , 36 , 37 , 38 ], essentially, for the analysis of nerve conduction velocity [ 33 , 39 ] and electromyography (EMG), to record the compound muscle action potentials (CMAPs) [ 33 , 40 , 41 , 42 ], which is considered the best diagnosis to evaluate neuropathies and myopathies [ 43 ].…”
Section: Diagnostic Assessment Of Nerve Repairmentioning
confidence: 99%
See 3 more Smart Citations
“…Regeneration is estimated to a rate of nearly about 1 mm/day [ 30 , 32 ] and different nerve conduction studies (NCS) have been used [ 33 , 34 , 35 , 36 , 37 , 38 ], essentially, for the analysis of nerve conduction velocity [ 33 , 39 ] and electromyography (EMG), to record the compound muscle action potentials (CMAPs) [ 33 , 40 , 41 , 42 ], which is considered the best diagnosis to evaluate neuropathies and myopathies [ 43 ].…”
Section: Diagnostic Assessment Of Nerve Repairmentioning
confidence: 99%
“…Electrodiagnostic testing in the clinical setting of a physiotherapy and rehabilitation center is not realistically easy to apply. However, it is possible to evaluate the nociceptive withdrawal reflex as an outcome measure [ 33 , 47 , 48 ] and also to document weight [ 36 , 49 , 50 , 51 , 52 ] and muscle mass as a sign of an increase in fiber diameter [ 38 , 53 , 54 , 55 , 56 , 57 ]. Assessments of functional recovery may be possible by video-based motion analysis that makes a precise evaluation of muscle function during locomotion [ 41 , 58 ].…”
Section: Diagnostic Assessment Of Nerve Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Physiologically, patients with traumatic nerve injury often do not benefit from physical therapy, 10 but success may be possible, since animal models have shown that exercise interventions can promote nerve and muscle regrowth. 11 Occupational therapy or related biopsychosocial interventions are recommended for rehabilitation after small fiber neuropathy, 12 and quality of life after peripheral nerve injury may depend on therapists' ability to help patients engage in meaningful work and household roles. 4,13 However, little of this research has explored specific consequences of unilateral impairment, because many clinical assessments were not designed to consider which hand was impaired.…”
Section: Introductionmentioning
confidence: 99%